Complex and underreported? A study into the prevalence of suicide by motor vehicle in the state of Queensland. (August 2021) - Yelo, D.; Parkes, A.; Freeman, J.; Davey, J.
Highlights: Up to a half of motor vehicle suicides may be unreported. Unreported and confirmed cases of motor vehicle suicide share many common factors. Unreported cases of motor vehicle suicide had a higher prevalence of females and multiple vehicle truck impacts compared to confirmed cases. Information pertaining to the driver's psychosocial history is missing or unavailable in many coroners reports of driver fatalities. A standardised procedure for conducting a psychological autopsy for motor vehicle suicide, may increase the accuracy of reporting the cause of such crashes. Abstract: While suicide is recognised as one of the leading causes of death in Australia, it is often presumed that fatal road crashes are primarily accidental in nature. However, international research has indicated that deliberate attempts at self-harm while driving may account for between 1.1% and 7.4% of road crashes. Despite the personal and financial costs associated with such events, few studies have examined the extent of motor vehicle suicides (MVS) or the circumstances surrounding such incidents in Australia. Given this, the current study reviewed coronial, police and toxicology findings of 762 motor vehicle fatalities in Queensland (Australia) during the period 2011 to 2015 to determine the frequency of confirmed cases and explore the prevalence (and characteristics) of possible MVS that remain undetected. In total, 22 confirmed cases were identified, and such events shared significant similarities with 14 possible events, including evidence of recent emotional upset, adversity and mental health diagnoses. In contrast, differences between the groups were limited to confirmed cases being more likely to involve males and contain a suicide note or evidence of past suicidality, while possible cases were more likely to involve a multiple vehicle impact with a truck. Importantly, crucial information regarding the deceased's psychological state and life circumstances (e.g., psychological autopsy) was not reported in many cases. Corresponding qualitative analysis of the coroners final determination (between the two groups) revealed the occurrence of the word suicide to occur seven times (31.8%) among confirmed cases and five times (35.7%) for possible casers. Furthermore, the coroners final determination of intent to suicide was open or undetermined in six of the possible cases (43%), which further suggests a reluctance (or procedural uncertainty) to categorically identify MVS. The paper further reviews the main findings, illuminates core challenges associated with identifying MVS and proposes a need for future investigations to incorporate a more standardised and evidence-based approach in order to effectively identify such events.